Familial occurrence of cervical artery dissection: coincidence or sign of familial predisposition? - Grond-Ginsbach, Caspar; Freitas, Gabriel R. de; Campos, Cynthia R.; Kloss, Manja (Cerebrovascular diseases, 2012)
Background and Purpose: The etiology of spontaneous cervical artery dissection (CeAD) is poorly understood in most patients. Mild cervical trauma preceding the dissection event is a common finding, but many CeAD occur spontaneously. It is likely that genetic factors may increase the risk for CeAD. However, familial cases are excedingly rare. Familial clustering of CeAD may be accidental or associated with genetic or environmental risk factors shared between affected relatives. In this explorative study, we aim to show that specific risk factors for familial CeAD exist. Methods: Age of onset, sex, affected artery and number of recurrent CeAD were documented for familial patients and compared with published findings from patients with sporadic CeAD. Concordance of age, sex and dissected artery within the families was analyzed by correlation analysis and by analysis of variance or Kruskal-Wallis testing. Results: The study sample consisted of 9 new patients with a family history of CeAD enrolled in the Neurology Department of the University of Heidelberg or referred to Heidelberg from other centers. The study sample also included published findings from another 23 patients, in total 32 patients. The mean age of the patients with familial CeAD at their first dissections was 38.4 ± 13.3 years. Twenty (62.5%) patients were female and 12 patients (37.5%) suffered multiple dissections. Four patients (12.5%) presented with recurrent dissections after >1 year. Patients with a familial history of CeAD were younger (p = 0.023) and presented more often with multiple dissections (p = 0.024) and recurrent dissections (p = 0.018). Age at the first event (correlation analysis p = 0.026; analysis of variance p = 0.029) and site of the dissection (correlation analysis p = 0.032; Kruskal-Wallis test p = 0.018) differed between the families, and there was no concordance of gender of affected family members (correlation analysis p = 0.500; Kruskal-Wallis test p = 0.211). Conclusions: The high prevalence of multiple dissection events and of long-term (>1 year) recurrent dissections in patients with a familial history of CeAD indicates that a specific predisposition for familial CeAD exists. Since age of onset and affected vessel differ between families, the risk profile for familial CeAD is heterogeneous. A large-scale (whole exome) sequencing analysis of 14 patients from 7 of the analyzed families is currently being performed in order to identify causative genetic variants.